Successful treatment of a patient with multiple solar keratosis (AK) with highly differentiated squamous cell carcinoma across the face through the combination of operation and photodynamic therapy: A case report - Xu Ji; Yuxin Ding; Li Ma; Jinchi Zhang; Mingkai Ji (Photodiagnosis and Photodynamic Therapy)
Actinic keratosis (AK) with multiple lesions on the face combined with well-differentiated squamous cell carcinoma is a severe skin lesion. Traditional treatment methods mainly rely on surgery. However, for a 92-year-old female patient, due to her advanced age and poor physical condition, traditional surgical treatment may bring significant risks and complications, such as postoperative infection and poor healing. Moreover, it is impossible to completely remove all AK lesions on the face through surgery, and surgical treatment may have a significant impact on the patient's appearance, potentially leading to facial scars, pigmentation, and other issues, which can seriously affect the patient's quality of life. Photodynamic therapy (PDT), as an emerging treatment method, can not only effectively reduce the size of the lesions but also improve the skin texture and color to some extent, offering a dual benefit.In this unique case, photodynamic therapy combined with surgery was successfully used to treat a 92-year-old female patient with multiple facial actinic keratoses (AK) and well-differentiated squamous cell carcinoma. The successful treatment of this case provides valuable reference for research in this field. However, the application of photodynamic therapy in treating complex skin lesions in elderly patients is still in the exploratory stage, and its long-term efficacy and safety are worth further investigation through clinical trials.